Characterizing Environmental Background Microflora and Assessing Their Influence on Listeria Persistence in Dairy Processing Environment - Vaishali Poswal; Sanjeev Anand; Brian Kraus (Foods)
Listeria monocytogenes (Lm) may persist in food processing environments (FPEs) alongside diverse background microflora. While microbial communities in FPEs can influence Lm survival, their role in supporting or suppressing its growth remains unclear. This study aimed to characterize the microflora in floor swabs and air samples collected from a dairy processing facility across three seasons and assess their potential impact on the growth of a Lm test strain previously isolated from a dairy processing environment. A total of 167 environmental isolates, representing 30 bacterial genera, were identified. Pseudomonas was consistently prevalent across all sample types. Seasonal shifts in bacterial genera were observed, with differences in microbial composition and relative abundance between production lines with and without Listeria innocua occurrence. Microflora distribution appeared more influenced by environmental and operational factors than by spatial proximity. Co-culture growth assays revealed no competitive exclusion of the Lm test strain, and no zones of inhibition were observed in antimicrobial assays using cell-free extract and dialyzed cell-free extract from environmental isolates against Lm. These findings suggest that Lm could potentially establish itself within mixed microbial communities in dairy processing environments, emphasizing the complexity of microbial interactions in FPEs and their potential role in Lm persistence.